Under His Majesty’s Protection: Orientational Metaphors in Neo-Assyrian Texts and Images - Portuese, Ludovico (Eikón / Imago, 2020)
In Orientational Conceptual Metaphor, a system of ideas is organized in the relation and interaction in space like up-down, in-out, front-back, on-off, deep-shallow, central-peripheral. Lakoff and Johnson (1980) called this group of metaphors “Orientational,” because they give a concept a spatial orientation: in the example, “happy is up,” the concept happy is oriented up leading to English expressions like “I’m feeling up today.” Such metaphorical orientations have a basis in our physical and cultural experience, thus they vary from culture to culture. Drawing on this theoretical and methodological framework, this paper argues for the existence of Orientational Metaphors in Neo-Assyrian sources, which are largely attested in textual and visual references concerning the relationships between king and subjects.